Safety and Recipient Satisfaction of Propofol Sedation in Outpatient Endoscopy: A 24-Hour Prospective Investigation Using a Questionnaire Survey - Yoshihide Kanno; Tetsuya Ohira; Yoshihiro Harada; Shinsuke Koshita; Takahisa Ogawa; Hiroaki Kusunose; Yoshiki Koike; Taku Yamagata; Toshitaka Sakai; Kaori Masu; Keisuke Yonamine; Kazuaki Miyamoto; et al. (Korean Society of Gastrointestinal Endoscopy, 2021)
Background/Aims The aim of this study was to evaluate the safety of sedation with propofol as an alternative to benzodiazepine drugs in outpatient endoscopy. Methods In this prospective study, examinees who underwent outpatient endoscopy under propofol sedation and submitted a nextday questionnaire with providing informed consent were evaluated. Periprocedural acute responses, late adverse events within 24 hours, and examinee satisfaction were evaluated. Results Among the 4,122 patients who received propofol in the 17,978 outpatient-based endoscopic examinations performed between November 2016 and March 2018, 2,305 eligible examinees (esophagogastroduodenoscopy for 1,340, endoscopic ultrasonography for 945, and total colonoscopy for 20) were enrolled, and their responses to a questionnaire were analyzed. The mean propofol dose was 69.6±24.4 mg (range, 20-200 mg). Diazepam, midazolam, and/or pentazocine in combination with propofol was administered to 146 examinees. Mild oxygen desaturation was observed in 59 examinees (2.6%); and mild bradycardia, in 2 (0.09%). Other severe reactions or late events did not occur. After eliminating 181 invalid responses, 97.7% (2,065/2,124) of the patients desired propofol sedation in future examinations. Conclusions Propofol sedation was found to be safe-without severe adverse events or accidents-for outpatient endoscopy on the basis of the patients' next-day self-evaluation. Given the high satisfaction level, propofol sedation might be an ideal tool for painless endoscopic screening.